Analisis Pengaruh Kredibilitas Influencer Marketing Terhadap Minat Beli Pada Industri Skincare Merek Lokal Indonesia - Arlin Tri Hastiana; Rifelly Dewi Astuti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
ABSTRACT The purpose of this study is to explore the influencers’ credibility dimensions (i.e. attractiveness, trustworthiness, expertise and similarity) on purchase intention through the mediating role of brand awareness, trust in influencer post, also cognitive and affective online engagement in Indonesian local brand skincare industry. The population of this study entails all social media users who have bought local skincare in Indonesia within 1 month and follow the influencers marketing who promote the brand in their social media account. The total number of respondents who were collected was 1,270 respondents, however only 968 respondents were taken for further measurements. The data was analyzed by SEM-PLS. The study demonstrates a very excellent fit for the data and the influence of expertise, trustworthiness, attractiveness, and similarity of influencer on brand awareness, trust in influencer’s post, online engagement, and purchase intention. This research is proved additional dimension of influencer credibility (similarity) besides three commonly used (expertise, trustworthiness and attractiveness). Another contribution of this research is that it succeeded in validating the credibility of which influencers influence the target market for local skincare brands in Indonesia. Keywords: Influencer Credibility, Brand Awareness, Trust, Engagement, Purchase Intention